2018
DOI: 10.1093/ntr/nty026
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, Smoking Cessation, and the Risk of Hearing Loss: Japan Epidemiology Collaboration on Occupational Health Study

Abstract: The prospective association between smoking and hearing loss has not been well studied. To the best of our knowledge, our study is the largest to date investigating the association between smoking and incident hearing loss. Our results indicate that smoking is associated with increased risk of hearing loss in a dose-response manner. Quitting smoking virtually eliminates the excess risk of hearing loss, even among quitters with short duration of cessation. These results suggest that smoking may be a causal fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
58
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 33 publications
11
58
2
Order By: Relevance
“…We retrieved data collected at 4 years before the event/index date. Data collection methods have been described in detail in previous papers . Smoking status was divided in to the following five groups: never smokers, past smokers, current low‐intensity smokers (1‐10 cigarettes/day), medium‐intensity smokers (11‐20 cigarettes/day), or high‐intensity smokers (≥21 cigarettes/day).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We retrieved data collected at 4 years before the event/index date. Data collection methods have been described in detail in previous papers . Smoking status was divided in to the following five groups: never smokers, past smokers, current low‐intensity smokers (1‐10 cigarettes/day), medium‐intensity smokers (11‐20 cigarettes/day), or high‐intensity smokers (≥21 cigarettes/day).…”
Section: Methodsmentioning
confidence: 99%
“…Data collection methods have been described in detail in previous papers. 10,11,13 Smoking status was divided in to the following five groups: never smokers, past smokers, current low-intensity smokers (1-10 cigarettes/ day), medium-intensity smokers (11-20 cigarettes/day), or high-intensity smokers (≥21 cigarettes/day). Hypertension was defined as systolic blood pressure of at least 140 mmHg, diastolic blood pressure of at least 90 mmHg, or use of treatment for hypertension.…”
Section: Covariatesmentioning
confidence: 99%
“…Sensitivity analyses were performed using different definitions of HL as follows: (1) pure-tone threshold at 0.5 kHz ≥ 25 dB in either ear, (2) pure-tone threshold at 1.0 kHz ≥ 25 dB in either ear 28 and (3) pure-tone threshold at 2.0 kHz ≥ 25 dB in either ear (separately) (Supplementary Tables S3 - S4 ). The incidence rate (95% CI) of HL at 0.5 kHz, 1.0 kHz, and 2.0 kHz were 4.9 (4.8–5.0) per 1000 person-years, 3.2 (3.1–3.3) per 1000 person-years, and 12.5 (12.3–12.8), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent cohort study of 1925 participants with a 15-year follow up, current smokers were more likely to cause HL than never-smokers (HR = 1.31, 95% CI = 1.003–1.71 in a model adjusted for age, sex, and education), but detailed information on smoking intensity, smoking duration, and other confounders was not available in this study 33 . In another cohort study of over 50,000 workers aged 20–64 years in Japan, the self-reported smoking status (current, former), smoking intensity (cigarettes smoked per day), and smoking pack-years were all significantly associated with an elevated risk of HL at an individual frequency (defined as > 30 dB at 1 kHz and > 40 dB at 4 kHz) after multivariable adjustment 28 . However, this study population was mainly composed of male workers (~ 85%), and information regarding important confounders including occupational noise exposure, alcohol drinking, and physical activity was only available in a subset of the study population 28 .…”
Section: Discussionmentioning
confidence: 98%
“…Typical risk factors for acquired hearing loss are trauma to the head and ear, excessive noise exposure (occupational and recreational), and aging 6 . Additionally, several studies have demonstrated that smoking is positively associated with risk of hearing loss disorder (HLD) 7-,9 , especially hearing loss at high frequencies with the attenuation of the association after smoking cessation among Japanese 10 : however, the results are not consistent 11,12 . One potential explanation for these inconsistent findings is that the relationship between smoking and HLD may be modified by other factors, including underlying genetic variation.…”
Section: Introductionmentioning
confidence: 99%